Pyrochlore glass-ceramics for the immobilization of molybdenum-99 production wastes: Demonstrating scalability and flexibility to waste stream variance. Issue 14 (November 2021) - Farzana, Rifat; Zhang, Yingjie; Dayal, Pranesh; Aly, Zaynab; Holmes, Rohan; Triani, Gerry; Vance, Eric R.; Gregg, Daniel J.
Graphical abstract: Abstract: Pyrochlore glass ceramics have been fabricated via in-situ crystallization under reducing conditions by both sintering and hot isostatic pressing (HIPing) as candidate wasteforms for the acidic waste biproduct of Mo-99 radiopharmaceutical production. The tailored wasteform demonstrates flexibility in the wasteform design to receive the required waste variability, it also suitably passes high-level waste performance requirement, and successfully scales to 1 kg scale with 45 wt.% waste loading. U-rich pyrochlore as the major phase was confirmed by X-ray diffraction, scanning electron microscopy and energy dispersive X-ray spectroscopy, with residual glass and minor secondary phases. The presence of both U 4+ and U 5+ valences in the wasteforms was revealed by diffuse reflectance spectroscopy. Addition of glass content had little influence on the pyrochlore composition but facilitated minor perovskite formation. The up-scaled dense, HIPed sample showed elemental releases of < 2 g/L for all elements in durability experiments.